1999
DOI: 10.1111/j.1600-0749.1999.tb00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Pheomelanin as a Binding Site for Drugs and Chemicals

Abstract: Certain drugs and chemicals, such as chloroquine, chlorpromazine, and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), are bound to melanin and retained in pigment cells for long periods. This specific retention in pigmented tissues can cause adverse effects in the skin, eye, inner ear, and pigmented nerve cells of the substantia nigra of the brain. To date, all studies have been focused on eu- and neuromelanin. In the present study, we show that chloroquine, chlorpromazine, chlomipramine, paraquat, acridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 25 publications
1
42
1
1
Order By: Relevance
“…The casing model (Fig. 1) is relevant in this respect in that pheomelanin is less efficient than eumelanin in binding drugs and metal ions (15). If pheomelanin were at the surface, the neuroprotective role of NM would not be expected.…”
Section: Implications Of Architecture Of Nmmentioning
confidence: 99%
“…The casing model (Fig. 1) is relevant in this respect in that pheomelanin is less efficient than eumelanin in binding drugs and metal ions (15). If pheomelanin were at the surface, the neuroprotective role of NM would not be expected.…”
Section: Implications Of Architecture Of Nmmentioning
confidence: 99%
“…In addition to chloroquine, severe retinopathies can occur following melanin binding by chlorpromazine. Chloroquine also accumulates in dermal melanocytes and hair follicles (79), where it can occasionally cause irreversible hearing loss, tinnitus, and dizziness (44). Whereas hearing loss due to chloroquine is thought to be a result of effects on the eighth cranial nerve, quinine can accumulate in melanin in the stria vascularis of the cochlea and cause cellular degeneration (74).…”
Section: Binding Of Compounds By Melanin In Humans In Vivomentioning
confidence: 99%
“…In the regions of highest neuronal loss, namely the SN, studies have shown an increase in iron levels in the late stages of PD (10). Based on these observations, NM's role in avidly chelating redox-active metal ions, toxic organic compounds, and free radicals would serve as a protective role (11)(12)(13). Neurons that produce catecholamines (dopamine, norepinephrine, etc.)…”
mentioning
confidence: 99%